Miracles of Saint Menas the Martyr: The Ethiopic Recension (Ta’ammera Minās, CAe 2386) - Rafał Zarzeczny (Vox Patrum)
The Ethiopic recension of the Miracles of Saint Menas the Martyr comprises nineteen episodes. The prologue attributes the compilation to Archbishop Theophilus of Alexandria. The Ge‘ez text derives from an Arabic source, although the specific original model remains unidentified. Currently, the Ethiopic text fully survives in three manuscripts, dating from the fifteenth to the seventeenth century. A modern paper copy also exists, made from the oldest extant codex. This publication offers the first complete translation of the Ethiopic collection; the edition of the Ge‘ez text will appear separately.